Interleukin-1-Interleukin-17 Signaling Axis Induces Cartilage Destruction and Promotes Experimental Osteoarthritis - Na, Hyun Sik; Park, Jin-Sil; Cho, Keun-Hyung; Kwon, Ji Ye; Choi, JeongWon; Jhun, Jooyeon; Kim, Seok Jung; Park, Sung-Hwan; Cho, Mi-La (Frontiers in Immunology, 2020)
Osteoarthritis (OA), which is the most common degenerative joint disorder, has been considered a non-inflammatory disease with abnormal mechanics. Interleukin (IL)-17 is a pleiotropic cytokine involved in inflammatory diseases and their production is driven by the cytokine including IL-1 and IL-23. However, little is known about the mechanism of IL-17 in the development of OA. Here, we investigated the role of IL-17 in the pathogenesis of OA using monosodium iodoacetate (MIA)-injected IL-17 and IL-1 receptor antagonist (IL-1Ra) double-deficient mice. In MIA-injected IL-1RaKO mice, nociceptive properties, degree of cartilage damage, and the level of inflammatory factors in articular cartilage were increased compared to MIA-injected wild-type mice. Interestingly, the intestinal architecture was impaired in IL-1RaKO mice compared to wild-type mice and the damage was further exacerbated by MIA injection. Deficiency of IL-17 reduced nociceptive properties and cartilage destruction, as well as inflammation-related factors in MIA-injected IL-1RaKO mice compared to MIA-injected wild-type mice. Furthermore, IL-17-treated chondrocytes from OA patients showed enhanced expression of catabolic factors that are involved in the destruction of cartilage in OA. IL-17 accelerates the destruction of cartilage and small intestine via regulation of several inflammatory mediators in an OA murine model. These results suggest that IL-17 plays a critical role in the development of OA.